E-210 A survey of medical students' perception of the neurointervention elective. (23rd July 2022) - Khalid, F; Rao, R; Oliver, M; Jumaa, M; Burgess, R; Zaidi, S
Abstract : Background: There is limited exposure to Interventional Neurology at the medical school level. To familiarize our medical students with this rapidly evolving field, the University of Toledo College of Medicine offers a two-week elective in Interventional Neurology (NIR) to the 4th year students. Since its inception in 2016, 37 students have taken this elective. This study surveyed these former elective students (ESs) to assess their perceived usefulness of a neuro-IR (NIR) elective. Methods: Of the 37 M4 students who completed the NIR elective, we found contact information for 25 ESs. An online 8 question survey was distributed via email to the students. Results: A total of 21 students completed the survey. Respondents self-identified as either applying to, in residency training, or having completed a residency in internal medicine (4.8%), neurology (81.1%), interventional radiology (4.8%), neurosurgery (4.8%), and orthopedic surgery (4.8%). The level of ESs training is either medical student (57%), PGY1 (4.8%), PGY2 (9.5%), PGY3 (14.3%), PGY4 (4.8%), PGY5 (4.8%), and attending (4.8%). Of all eESs, 85.7% felt the elective rotation reinforced their choice of residency. Refer to the table for survey details. Conclusion: Our survey findings suggest that providing a designated NIR elective for medical students may give the proper direction for trainees to make decisions regarding their residency training. Furthermore, an early orientation may attract medical students to NIR as a career choice. In addition, our survey demonstrates the benefit of a neuro-IR elective in terms of managing cerebrovascular patients. Disclosures: F. Khalid: None. R. Rao: None. M. Oliver: None. M. Jumaa: None. R. Burgess: None. S. Zaidi: None.